2021
DOI: 10.3390/agriengineering3010006
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Basil (Ocimum basilicum) in DRF, Raft, and Grow Pipes with Effluents of African Catfish (Clarias gariepinus) in Decoupled Aquaponics

Abstract: Basil (Ocimum basilicum) was cultivated in Rostock, Northern Germany, in a decoupled aquaponic system with African catfish (Clarias gariepinus) under intensive rearing conditions by using three hydroponic components, the dynamic root floating technique (DRF), the raft technique, and grow pipes. A 25% of the recommended feed input still allowed African catfish growth and provided adequate nitrogen and calcium levels in the process water. After 36 days, the plants were examined with respect to 16 different growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Inevitably, the demand for basil is considerably high among both hydroponics and aquaponics producers. Studies indicate that owing to its characteristics, basil is the most used herb for different hydroponics and aquaponics experiments [18]. Basil produces 1.8 kg per meter square under aquaponic production, and only 0.6 kg per meter square in soil cultivation [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inevitably, the demand for basil is considerably high among both hydroponics and aquaponics producers. Studies indicate that owing to its characteristics, basil is the most used herb for different hydroponics and aquaponics experiments [18]. Basil produces 1.8 kg per meter square under aquaponic production, and only 0.6 kg per meter square in soil cultivation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that basil has a lot of characteristics and properties that make it one of the most common herbs used extensively in the kitchen as well as in several other business sectors [15,18,20]. Nevertheless, while previous researchers found that basil production and yield is higher in the case of aquaponic systems than in soil systems, no information is available on the level of antioxidants present in basil grown in both systems.…”
Section: Introductionmentioning
confidence: 99%
“…Option 2 integrates a highly productive 10,000 m 2 basil greenhouse with artificial lighting for year-round production. Basil has already achieved promising results in aquaponics [24]; only small amounts of additional fertilisation, especially with potassium and iron, would be necessary [25,26]. The greenhouse (returns 248,502 EUR/year; ROI 6.93%) together with aquaculture would result in returns of 284,502 EUR/year and an ROI of 6.26%.…”
Section: Entrepreneurial Decision Scenariosmentioning
confidence: 99%
“…This is nowadays recognised also on German markets, seeking new investments into African catfish RAS and further increasing production capacity. In addition, several studies demonstrated that African catfish effluents can be used in aquaponics to produce valuable plant products such as basil (Ocimum basilicum) [24][25][26], mint (Mentha spicata) [27] and pumpkin (Telfairia occidentalis) [28]. However, the development of African catfish farms in Germany were primarily promoted by the European Maritime and Fishery Fund (EMFF) [29] in the form of investment subsidies of up to 49%, but were also supported by the Renewable Energy Law (EEG), where the use of warm water from biogas production inside the RAS was compensated with an additional subsidy (Combined Heat and Power bonus-CHP) [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Fruiting crops, such as tomatoes (Solanum lycopersicum) or cucumbers (Cucumis sativus), are often cultivated in nutrient-film-technique (NFT) systems [4,5]. Basil (Ocimum basilicum) grew best in an ebb-and-flood gravel substrate system compared to grow pipes (similar to NFT) and raft; [6]) and showed good growth performance with the dynamic root floating technique (DRF; [7]) and in aeroponics [8]. An international study in 2015 showed an earlier preference for raft and media bed components for aquaponic crops [9].…”
Section: Introductionmentioning
confidence: 99%